Interlaboratory comparison tests in mineralogical works - Elena G. Ozhogina; Maria I. Lebedeva; Elena A. Gorbatova (Стандартные образцы)
Introduction. Activities of FSBI “VIMS” are aimed at ensuring accuracy and comparability of the results of mineralogical analyses accompanying exploration and technological work. Evaluation of the research result quality is carried out with the help of various metrological instruments, one of which is an interlaboratory comparison test.Purpose. The purpose of interlaboratory comparison tests (ICTs) is to assess the results of X-ray quantitative phase analysis of an artificial mixture of minerals and to confirm the level of competence of testing laboratories.Methods. The procedure for conducting interlaboratory comparison tests is as follows: development of the programme and its approval; collecting and registering applications from laboratories, willing to participate in the ICT programme; preparation and simultaneous sending of control samples with accompanying information materials to those participating in the experiment; statistical processing of obtained results; drawing up, approval and circulation of documents confirming participation of the laboratories. The control sample is a homogenized artificial mixture of minerals (quartz, kaolinite, calcite and pyrite). The accuracy (quality) control of test results was carried out by X-ray quantitative phase analysis.Results. The ICT results showed a high level of competence of testing laboratories. For unreliable and unsatisfactory results percentages total less than 11%, the percentage for unfulfilled results is equal to zero. Interlaboratory comparison tests in mineralogical works are an important means for controlling competence of testing laboratories.